Efectos de fertilizantes de liberación controlada en el rendimiento del cultivo de maíz (Zea mays L.) bajo dos densidades de siembra, en la zona de Babahoyo - Limones Díaz, Christian Víctor (2018)
VIII. SUMMARY The present experimental work was carried out in the lands of the experimental farm of the Ability of Agricultural Sciences of the Technical University of Babahoyo in the sector San Pablo, located in Km 7,5 of the road Babahoyo-Montalvo. Ten treatments and three repetitions were investigated. The objective of the experimental work was to evaluate the agronomic behavior of the corn with the application of fertilizers of controlled liberation, to determine the answer and its effect on the production of the cultivation. The crop of corn was carried out with the hybrid insignia 105 in parcels of 20 m2. The treatments were distributed in a design of divided parcels. For the evaluation of stockings the test was used from Tukey to 5 % significance. The evaluated variables were: flowering, plant height, height of ear insert, diameter and longitude of ears, weight of 100 grains, grain yield and economic analysis. The results determined that the agronomic characteristics were partially influenced with the application of the fertilizers with increment of the yield of 80,86 %. Likewise, when comparing the populational densities an increment of 18,63% it exists that is due to the increment of plants, being demonstrated the importance handling of populations in the cultivations to increase the grain production. The Witness presented the lowest averages in the studied variables. Keywords: Fertilizer effect, performance, planting density, controlled release of the corn crop.